Breather wave, lump-periodic solutions and some other interaction phenomena to the Caudrey-Dodd-Gibbon equation - Yusuf, Abdullahi; Sulaiman, Tukur Abdulkadir; İnç, Mustafa; Bayram, Mustafa (Springer Heidelberg, 2020)
Hirota's bilinear method is used in this paper to obtain some breather wave and lumps solutions to the Caudrey-Dodd-Gibbon equation through the symbolic Mathematica 12 package. This equation is converted into its potential version and then the transformation of Cole-Hopf is implemented on the equation to produce its bilinear form. We then formally derive some novel solutions such as breather-wave, lump-periodic and some interaction solutions. The details explanation of the acquired solutions are also illustrated graphically in order to show the physical features of the solutions.
Keywords: Nonlinear Evolution-Equations; Solitons; Dynamics